Early Detection and Modern Treatment Methods of Congenital Heart Defect - Tolmasovich, Tolmasov Ruzibek; qizi, Yusupova Dilroz Hamdam (American Journal of Biomedicine and Pharmacy, 2025)
This article discusses congenital heart disease, its causes, symptoms, and prevention. In addition, we will introduce modern diagnostic and treatment methods depending on the type of pathology and the general condition of the child. The issue of early detection of congenital heart disease, which is very important for improving the quality of life of the child and preventing serious complications, is raised. We will consider the genetic and environmental factors that mainly affect this disease. There are several types of congenital heart defects, depending on their anatomical location and the effect on blood flow. We will dwell on each of them below. Heart defects are the most common congenital defects and are the main cause of death in children due to developmental defects.